2009
DOI: 10.3155/1047-3289.59.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Measurement: The Use of Optical Light Scattering for the Determination of Particulate Size Distribution, and Particulate Mass, Including the Semi-Volatile Fraction

Abstract: The GRIMM model 1.107 monitor is designed to measure particle size distribution and particulate mass based on a light scattering measurement of individual particles in the sampled air. The design and operation of the instrument are described. Protocols used to convert the measured size number distribution to a mass concentration consistent with U.S. Environmental Protection Agency protocols for measuring particulate matter (PM) less than 10 microm (PM10) and less than 2.5 microm (PM2.5) in aerodynamic diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
132
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(135 citation statements)
references
References 5 publications
3
132
0
Order By: Relevance
“…For non-spherical particles the function is more complex and several methods such as the Discrete Dipole Approximation can be employed (Yurkin and Hoekstra, 2007). The GRIMM Spectrometer model EDM 164 employed in the present work uses multi-channel light scattering optics as the measuring principle; a detailed description with schematic diagrams of a similar instrument can be found in Grimm and Eatough (2009). The instrument is provided with a laser diode emitting at γ = 660 nm.…”
Section: The Grimm Aerosol Optical Spectrometermentioning
confidence: 99%
See 1 more Smart Citation
“…For non-spherical particles the function is more complex and several methods such as the Discrete Dipole Approximation can be employed (Yurkin and Hoekstra, 2007). The GRIMM Spectrometer model EDM 164 employed in the present work uses multi-channel light scattering optics as the measuring principle; a detailed description with schematic diagrams of a similar instrument can be found in Grimm and Eatough (2009). The instrument is provided with a laser diode emitting at γ = 660 nm.…”
Section: The Grimm Aerosol Optical Spectrometermentioning
confidence: 99%
“…The instrument is provided with a screened entrance head in accordance with Johannesburg Convention which, in accordance with the manufacturer, permits efficient entrance of particles of sizes up to 10-20 μm, for wind speeds up to 8 m.s −1 (Grimm and Eatough, 2009). …”
Section: The Grimm Aerosol Optical Spectrometermentioning
confidence: 99%
“…The corresponding measurement principle relies on the properties of light scattered by particles injected in an optical chamber and crossing a light beam (e. g. Grimm and Eatough, 2009). The measurements are usually conducted at "large" scattering angles, typically around 90 • with collecting angle of a few tens of degrees.…”
Section: Introductionmentioning
confidence: 99%
“…The mass M A (ng m −3 ) and number N A (cm −3 ) concentrations of aerosol particles with diameters from 0.3 to 20 µm were determined with the help of photoelectric particle counters GRIMM 1.108 (Peters et al, 2006;Grimm and Eatough, 2009) and AZ-10 (Manual AZ-10, 2010), which were calibrated under factory conditions with the help of polystyrene latexes with known sizes. The intercalibration of photoelectric counters, performed before the expeditions, confirmed that data compare well within the uncertainties of the instruments.…”
Section: Characterization Of Expedition Measurementsmentioning
confidence: 99%